The EFFECT OF TRANSFORMATIONAL LEADERSHIP STYLE, WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Bahiroh, Eloh; Khoiri, Rizki Waladun; Arthawati, Sri Ndaru (Management Science Research Journal, 2022)
This research aims to determine the effect of transformational leadership style, work environment, and work motivation on the performance of employees of PT. Dwi Putra Selaras in Cilegon City. The research method used is quantitative. This study collects data based on a questionnaire with measurements using an interval scale. and using 93 respondents as a sample as well as a population or called non-probability sampling (saturated sample). The data analysis method used is the SmartPLS 3.0 analysis tool which consists of instrument testing and outer and inner model tests. From the results of data calculations that have been carried out using SmartPLS 3.0, it can be concluded: (1) there is no significant effect of transformational leadership style on employee performance (2) there is a positive and significant effect of the work environment on employee performance (3) there is a positive influence and the significance of work motivation on employee performance.